Rediscovering Earthworms - Mishra, C. S. K., 1963- (Cambridge Scholars Publisher, 2021)
This book is a concise and well-illustrated treatment of the conventional knowledge and modern utilities of earthworms. The first two chapters deal with earthworm morphology, food relationship, behavior, functional role, interaction with soil biota, and the influence of environmental factors. Earthworms found in the tropics and sub-tropics are also discussed in this section. The third chapter provides a good account of utilizing species of worms to produce high value manure through vermitechnology and its application in agriculture. The nutritional and medicinal values of earthworms are illust.